2015
DOI: 10.4238/2015.july.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variation of Sporisorium scitamineum in Mainland China revealed by internal transcribed spacers

Abstract: ABSTRACT. Sugarcane smut caused by the fungus Sporisorium scitamineum is a worldwide disease and also one of the most prevalent diseases in sugarcane production in mainland China. To study molecular variation in S. scitamineum, 23 S. scitamineum isolates from the 6 primary sugarcane production areas in mainland, China (Guangxi, Yunnan, Guangdong, Hainan, Fujian, and Jiangxi Provinces), were assessed using internal transcribed spacer (ITS) methods. The results of ITS sequence analysis showed that the organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…The ITS sequencing data was even more inefficient, producing identical sequences for all strains, including those from Argentina. The ITS data produced by other authors revealed some variability in isolates from different countries (Singh et al, 2005;Zhang et al, 2015). After align our data with other 30 ITS sequences available at genbank, the Brazilian and Argentine haplotypes were equal to the most common haplotype worldwide (Fig.…”
Section: 1) Molecular Variability Of S Scitamineum Unraveled By Afsupporting
confidence: 59%
See 1 more Smart Citation
“…The ITS sequencing data was even more inefficient, producing identical sequences for all strains, including those from Argentina. The ITS data produced by other authors revealed some variability in isolates from different countries (Singh et al, 2005;Zhang et al, 2015). After align our data with other 30 ITS sequences available at genbank, the Brazilian and Argentine haplotypes were equal to the most common haplotype worldwide (Fig.…”
Section: 1) Molecular Variability Of S Scitamineum Unraveled By Afsupporting
confidence: 59%
“…Many genetic studies have been conducted on global and local levels, using different strategies to assess S. scitamineum molecular variability and virulence degree (Bhuiyan et al, 2015;Fattah et al, 2010;Luzaran et al, 2012;Que et al, 2012;Raboin et al, 2007;Rago et al, 2009;Singh et al, 2005;Xu et al, 2004Xu et al, , 2014Zhang et al, 2015). In an overall view, low levels of genetic variation were found in American and African isolates while high levels were found in Southeast Asian populations.…”
Section: ) Sugarcane Smut Diseasementioning
confidence: 99%
“…Similarly, the number of LGs in the susceptible parent L 99-226 (137) was expectedly more than the ideally expected number 120. Such genetic map fragmentation in L99-226 could be due to a lower number of polymorphic markers due to inbreeding-caused reduced heterozygosity in modern sugarcane ( Deren, 1995 ), and low marker density and uneven distribution of linked SD markers. In addition, the high number of recombinant linkage groups in the present study could be attributed to the small mapping population size.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and concentration of DNA was analysed by 1% agarose gel electrophoresis and a nanodrop spectrophotometer. To verify the identity of the fungus, the DNA that was extracted from the samples was ampli ed on conventional PCR using the bE4 (5'-CGCTCTGGTTCATCAACG − 3') and bE8 (5'-TGCTGTCGATGGAAGGTGT − 3') primers that are speci c for S. scitamineum (Zhang et al, 2015).…”
Section: Pathogen Veri Cationmentioning
confidence: 99%
“…The DNA was sent for sequencing at Inqaba Biotech, South Africa. Sequencing was based on the ITS region of the fungal genomic DNA using the ITS1 (5'-TCCGTAGGTGAACCTGCGG − 3') and ITS4 (5' -TCCTCCGCTTATTGATATGC − 3') primer pair (White et al, 1990;Zhang et al, 2015). The ITS target region was ampli ed using OneTaq® Quick-Load® 2X Master Mix (NEB, Catalogue No.…”
Section: Dna Extraction Ampli Cation and Sequence Analysismentioning
confidence: 99%